ANALISIS UPAYA PEMASARAN (MARKETING EFFORTS) BERDASARKAN SEGMENTASI PASAR DARI ASPEK GENDER TABUNGAN BRITAMA PADA PT. BANK RAKYAT INDONESIA (Persero) Tbk KANTOR CABANG METRO - Melan Susanti Purnamasari (Business Perspective Journal, 2021)
The economic crisis has made a lot of banks find difficulty in maintaining the customers to have always made use of banking service. It’s suggested that marketing efforts which could understand the customers desire more need to be made so that the relation between the bank and the customers would increase and it will contribute to the profit. The result of analysis shows that for female, the variables of price marketing mix (X2), employees (X5), and process (X6) are significantly influenced the length of savings time, while the variables of product (X1), promotion (X3), place (X4), and physical infrastructure (X7) are not significant. On the other hand, for male, only two variables, i.e. employees (X5) and process (X6) show significant influenced to the length of saving time while the variables of product (X1), price (X2), promotion (X3), place (X4), and physical infrastructure (X7) are not significant. Keyword: Marketing Efforts, Market Segmentation.